تقييم نوعية المياه الجوفية باستخدام مؤشر جودة المياه بمنطقة سوق الثلاثاء –زليتن - اليعقوبيد.فتحي خليفة; خليفةم.أسامة محمد (Aljameai, 2023)
المستخلص: تعتبر منطقة سوق الثلاثاء بمدينة زليتن من المناطق التي تشهد نمو سكانيا وقد نتج عن هذه الزيادة تزايد النشاط الزراعي والصناعي والذي يترتب عليه الزيادة في استهلاك المياه الجوفية وتتعرض هذه المياه لتداخل مياه البحر نتيجة لسحبها بكميات كبيرة تفوق كميات التغذية مما ادى الي تدني نوعيتها. وأظهرت نتائج التحاليل الكيميائية لعينات مياه الآبار ان هناك زيادة في تركيز مجموع الأملاح الذائبة TDS حيت تراوحت ما بين 1313ppm الي 2500ppm. وزيادة في تركيز الصوديوم Na+ من 339ppm الي 558ppmبينما تركيز الكلوريد-Cl تتراوح من 1218ppm الى 2838 ppm والنتائج كلها تتجاوز الحد المسموح بها طبقا للمواصفات القياسية الليبية للمياه الشرب. بينما مؤشر جودة المياه (WQI) أوضح ان جميع الآبار ذات مياه رديئة، عدا البئر W1 فمياه جيدة، ونتائج نسبة جونز تشير إلى وجود تداخل للمياه البحر. Abstract The suq tholta area in the city of Zliten is witnessing a population growth, and an increase in agricultural and industrial activity, which leads to an increase in the consumption of groundwater. The results of chemical analyzes of well water samples showed that there was an increase in the concentration of total dissolved salts (TDS), ranging from 1313ppm to 2500ppm. And an increase in the concentration of sodium Na+ from 339 ppm to 558 ppm, while the concentration of chloride Cl- ranged from 1218 ppm to 2838 ppm, and all results exceed the permissible limit according to the Libyan standard specifications for drinking water. While the Water Quality Index (WQI) showed that all wells have poor water, except for well W1, which has good water, and the results of the Jones ratio indicate that there is an overlap of sea water.